Scenes, Spaces, and Memory Traces: What Does the Hippocampus Do?. (October 2016) - Maguire, Eleanor A.; Intraub, Helene; Mullally, Sinéad L.
The hippocampus is one of the most closely scrutinized brain structures in neuroscience. While traditionally associated with memory and spatial cognition, in more recent years it has also been linked with other functions, including aspects of perception and imagining fictitious and future scenes. Efforts continue apace to understand how the hippocampus plays such an apparently wide-ranging role. Here we consider recent developments in the field and in particular studies of patients with bilateral hippocampal damage. We outline some key findings, how they have subsequently been challenged, and consider how to reconcile the disparities that are at the heart of current lively debates in the hippocampal literature.